Aluminum in silica phases formed in hot springs - Hinman, Nancy W.; Kotler, J. Michelle (Procedia Earth and Planetary Science, 2013)
Sinters are difficult to characterize with traditional methods and are often described by their chemical composition alone. Yet information about the depositional environment and possible diagenetic processes is available in atomic structure. This study probes the atomic structure of siliceous sinters from two geothermal areas using nuclear magnetic resonance (NMR) spectroscopic techniques. Specifically, this study demonstrated that Al is present in tetrahedral coordination with or without octahedral coordination in geyserites from Yellowstone National Park, WY, USA and Geyser Valley, Kamchatka, Russia.